Gonadal dysfunction and beyond: Clinical challenges in children, adolescents, and adults with 47, XXY Klinefelter syndrome. Issue 2 (16th May 2020) - Zitzmann, Michael; Rohayem, Julia
Abstract: Klinefelter syndrome (KS) is the most frequent sex chromosomal aneuploidy. The karyotype 47, XXY originates from either paternal or maternal meiotic nondisjunction during gametogenesis. KS males are very likely to exhibit marked gonadal dysfunctions, presenting both in severely attenuated spermatogenesis as well as hypergonadotropic hypogonadism. In addition, neurocognitive and psychosocial impairments, as well as cardiovascular, metabolic and bone disorders are often found in KS and might explain for an increased morbidity/mortality. All conditions in KS are likely to be induced by both gene overdosage effects resulting from supernumerary X‐chromosomal genes as well as testosterone deficiency. Notwithstanding, the clinical features are highly variable between KS men. Symptoms can become obvious at infancy, childhood, or adolescence. However, the majority of KS subjects is diagnosed during adulthood. KS adolescents require specific attention regarding pubertal development, in order to exploit their remaining fertility potential and allow for timely and tailored testosterone replacement. The chances for sperm retrieval might decline with age and could be hampered by testosterone replacement; therefore, cryostorage of spermatozoa is an option during adolescence, before the decompensation of endocrine and exocrine testicular functions becomes more overt. Sperm from semen or surgically retrieved, in combination with intracytoplasmic sperm injection enables KS males to become biological fathers of healthy children. The aim of this article is to present the current knowledge on KS, to guide clinical care and to highlight research needs.